Antimicrobial activity of methyl gallate isolated from the leaves of Glochidion superbum against hospital isolates of methicillin resistant Staphylococcus aureus - Ahmed, Mohammed Dahiru; Bakhtiar, Muhammad Taher; Maimusa, Alhaji Hamusu; Rezali, Mohd Fazlin; Mustafa Mahmoud, Mohammed Imad Al-Deen (Korean Society of Pharmacognosy, 2017)
An antimicrobial compound has been isolated from the leaves of Glochidion superbum. The compound was determined as methyl 3, 4, 5-trihydroxybenzoate (methyl gallate), based on ultraviolet (UV), infrared (IR), nuclear magnetic resonance (NMR) and mass spectroscopy (MS) analysis. The isolated compound exhibited potent antimicrobial activity against three clinical isolates of methicillin resistant Staphylococcus aureus (MRSA) by qualitative agar disc diffusion method and quantitative broth dilution method. Agar disc diffusion was done in a dose-dependent manner for each bacterial isolate at disc potencies of 25, 50, 100, and 150 µg/disc. The zones of inhibition were on average equal to 12.27, 14.20, 15.43, and 24.17 mm respectively. The inhibition zones were compared with that of vancomycin disc at 30 µg as a reference standard. The MIC and MBC values were 50 µg/mL and 100 µg/mL respectively. The results of anti MRSA activity were analyzed using one-way ANOVA with Turkey’s HSD and Duncan test. In conclusion, methyl gallate which was isolated from G. superbum showed the inhibition activity against methicillin resistant S. aureus